Formation of Indicators of Resultativity and Effectiveness of Business Processes on the Basis of the Balanced Scorecard (BSC) Concept - Черчата, А. О. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article analyses and estimates performance and efficiency of enterprise’s business processes, as performance and efficiency defines different aspects of business processes functioning. The investigation states, that four criteria using (financial and economic criterion, manufacturing (resource) criterion, external integration criterion, organizational criterion), that are the part of the adapted to field balanced scorecard are useful to estimate performance and efficiency of enterprise’s operating business processes. Definite performance and efficiency estimating activities were formed for each proposed criterion, considering peculiarities of each enterprise’s operating business processes.